The Analysis of Implementing Safety Management System (SMS) to Improve The Flight Safety - Poerwanto, Eko (SENATIK STT Adisutjipto, 2019)
Flight safety can be created only by good cooperation from all stakeholders in aviation. In other words, each flight stakeholder has the responsibility and contribution to the flight safety. This condition shows the importance of analyzing the implementation of Safety Management System (SMS) in the aviation industry, because it is a part of the State Safety Program (SSP) in accordance with ICAO standard. The research method is presented descriptively related to the aviation safety regulations with the current conditions of implementing flight safety. The results showed the implementation of the Safety Management System (SMS) by each flight stakeholder was running, but the "Flight Safety Promotion" activity had not been able to run properly, because there were no periodic reports issued by regulators on the Aviation Safety Program. Another thing is the violation of the implementation of Safety Management System (SMS) has not been through the "Aviation Professional Assembly", so that the personnelwho committedthe violations will get objective punishment.